Variación espacio-temporal del vapor de agua precipitable (PWV) en la costa norte del Perú para el periodo 2001-2017 - Guerrero Salinas y Cols., Jhon Brayan (2019)
The objective of this study was to perform the analysis of the spatial and temporal variability of the precipitable water vapor column (PWV) on the northern coast of Peru (3°S-7°S). A total of 17 years of PWV data obtained from the MODIS/Terra sensor were analyzed, from which maps of provisional climatology and standard deviation were generated, in order to obtain the patterns of average spatial distribution and temporal variability. The provisional climatological map of PWV shows in general that the areas with the greatest variability of PWV are found in the ocean and lowlands, while the areas of least variability are found in the Andes region. The Hovmöller diagrams and the time series identified an annual cycle and the increase of the extreme values in the summer months from the year 2010. The power spectral analysis of the time series apart from identifying the annual period also identifies a period semiannual that is due to the seasonal change summer-winter.